Branding analysis of Brawijaya University vocational education - Asri, Tri Mega; Putri, Debri Haryndia; Septian, Muhammad Daniel (Universitas Padjadjaran, 2023)
Background: The current challenge in Indonesia is the rising unemployment rate of college graduates and low interest in continuing to study at university, especially in Vocational Faculty. Therefore, the university must clearly understand what potential prospective students are looking for. The Vocational Faculty consists of two departments: the Department of Business and Hospitality and the Department of Creative and Digital Industries. In the 2021 class, the total number of students are 499 students. Purpose: This research aims to assess equity of UB Vocational brand in the eyes of prospective students. In this study, candidate students, namely students of SHS/ Vocational School in third grade whose planning to continue studying in college and new students of UB Vocational. Methods: The research method used in this research is descriptive. The data acquisition technique in this study was using open questionnaire. Results: Brand Image, related to the Vocational Education of Brawijaya University, which produces graduates who are ready for work and satisfied with the institution, is assessed in terms of educational attributes, including the quality of lecturers, facilities, curriculum, and cooperation. Conclusion: The main objective of this study is to assess the determinants of university brand loyalty by mapping out the characteristics regarding respondents’ reaction to higher education services (especially universities) at the Vocational Faculty of Brawijaya University through measuring brand awareness, image, and satisfaction. Implications: The results of this research shows that the Vocational Education of Brawijaya University as a place to continue study for new candidate students are still being recognized and considered as one particular choice to for higher education.